Association of prognostic nutritional index and severe abdominal aortic calcification in middle-aged adults: a cross-sectional study - Yuanming Li; Jing Tang; Yi Zhou; Lishan Bai (BMC Cardiovascular Disorders)
Abstract Background The prognostic nutritional index (PNI) serves as an indicator of systemic inflammation, immunological function, and nutritional condition in individuals. The aim of this study was to investigate the potential association between PNI and severe abdominal aortic calcification (SAAC) in middle-aged adults. Methods The study included 1,436 subjects aged 40–60 years (average age 49.72 years, with females representing 50.97%) from the 2013–2014 NHANES. AAC scores greater than 6 is defined as SAAC. PNI was defined as 5× Lymphocyte Count (10^9/L) + Serum Albumin (g/L). To investigate the independent association of PNI with SAAC, we performed weighted multivariable logistic regression analyses using NHANES sampling weights to account for the complex survey design. We constructed three progressively adjusted models: Crude model, Model 1 (age/sex/race-adjusted), and Model 3 (fully adjusted for all covariates). Additional stratification analyses and interaction examinations were conducted to evaluate potential modifying effects of confounding variables. For nonlinear analyses, we employed restricted cubic splines (RCS) with 4 knots at the 5th, 35th, 65th, and 95th percentiles to flexibly model the dose-response relationship between PNI and SAAC probability. The nonlinearity was tested using likelihood ratio tests comparing the linear and spline models. We further assessed the association between PNI and SAAC in hypertensive subgroups using generalized additive models and smoothed curves. Sensitivity analyses to determine the robustness of the PNI and SAAC association results. Results In fully adjusted models, each unit increase in PNI was also associated with a 11% increase in the risk of SAAC occurrence [OR (95% CI): 1.11 (1.07, 1.16)]. Subgroup analyses showed that the relationship between PNI and SAAC was modified by hypertension (P-interaction < 0.0001). In the nonhypertensive population, the association between PNI and SAAC was significantly positive. Conclusions We found that nutritional status combined with inflammation did not have a protective effect on SAAC. Conversely, in middle-aged individuals (especially those without hypertension), higher PNI scores were associated with a higher risk of SAAC, which was unexpected.